Features Reproductive Health in pregnant women attending a service differentiated care for adolescents - Lucich, E. (2015)
To identify characteristics of reproductive health in a group of teenagers pregnant. DESIGN: Transversal descriptive study. Materil AND METHODS: 400 edolescentes randomly chosen (13-18 years), gestation to term, without mental nor physical alterations, performing one interview previously validated. RESULTS: Mean age 17 ± 1.56 (13-18) years, menarche 13 ± 1.7 (8-18) years, first sexual intercourse 15 ± 1.34 years, with the father of the newborn (75.2%) 2.75% rape (11 cases). Reason for first intercourse: shared with partner (43.7%), then referring fear 18%, shame 14.7%, repentance 10% desire. 87% reported sexual partners, 13% from 2 to 5. 54.5% had no prior information about sexuality, only 6% knew their fertile period, 45% the process of fertility. 27% do not know any method of family planning: 78% know about AIDS and 20.7% ignore about other STDs. CONCLUSIONS: Adolescents with poor knowledge on reproductive health, acquired mainly in schools, family and health institutions; not responsibly assume their sexuality, reflected in negative attitudes and feelings of group pressure and / or partner. Scarce information on family and ETS planning.